Combining Rock-Eval® thermal analysis and thermochemolysis to evaluate the influence of forest management on soil organic matter quality and stability. (May 2023) - Sun, Zheng; Quénéa, Katell; Delarue, Frédéric; Anquetil, Christelle; Ravelojaona, Herman; Sebag, David; Eon, Loic; Kowalewski, Isabelle
Highlights: Forest management practices can lead to distinct compositions of topsoil OM. Thermal stability is likely constrained by mineral interactions. Thermal analysis and Py-GC/MS highlight forest management impacts on OM. Abstract: The effect of forest management practices on carbon quality is poorly documented. To assess changes in the quality and stability of soil organic carbon (SOC) of a temperate forest upon human activities, we investigated soil from forests (i) developed following natural regeneration after clearcutting 20 and 40 years ago, (ii) developed following afforestation on an abandoned crop area 40 years ago and (iii) in an area where regular clear-cut (with wood residues input) was conducted 40 years ago. Topsoil and subsoil layers were collected (0–20 cm and 50–80 cm). Soil organic matter (OM) was characterized by elemental analysis (total carbon and total nitrogen), thermal analysis (Rock-Eval®) and thermochemolysis (i.e., Py-GC/MS in the presence of tetramethylammonium hydroxide (TMAH)). In addition, a size fractionation to separate the labile coarse fraction (50–2000 μm) from the fine fraction (<50 µm) was performed. These fractions were analyzed by thermal analysis. Despite no measurable differences in carbon and nitrogen contents, the characterization of the OM by thermal analysis, and the relative quantification of OM compounds revealed differences in the composition in OM for the topsoil layers. The thermal analysis clearly distinguished sites with inputs of woody residues (higher HI) with a higher relative contribution of lignin and cutin/suberin compounds. However, the OM thermal stability seems mainly controlled by the organo-mineral interactions rather than chemical composition. Combination of Rock-Eval® thermal analysis and Py-GC/MS suggests that thermal stability cannot be used as an indicator of stability in specific contexts where pedogenetic processes are deeply modified by regular and extensive anthropogenic inputs of woody residues.